Zenobia: an absent myth (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Contrary to Cleopatra, Zenobia has never gained a prominent place in the collective imaginary. Nonetheless, the queen, remembered for having opposed herself to emperor Aurelian, appeared in many works of fiction from Petrarca on, and she has recently being rediscovered in the Arab culture as a symbol of the opposition to the Western imperialism.
Keywords: zenobia; cleopatra; queen; arabic world; imperialism